2012
DOI: 10.1177/193229681200600102
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hyperglycemia, Glucocorticoids, and Insulin Use with Morbidity and Mortality in the Pediatric Intensive Care Unit

Abstract: Background: Studies of pediatric intensive care unit (PICU) patients have shown a significant association of morbidity and mortality with hyperglycemia. We retrospectively evaluated the degree of hyperglycemia as well as its correlation with glucocorticoid and insulin use and assessed its association with hospital length of stay (LOS) and mortality. This study preceded the initiation of a standard glycemic control protocol. Methods: We examined medical records at Kosair Children's Hospital for all PICU admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…To evaluate the relationship between early blood glucose concentrations and PICU mortality and to define a ‘safe range’ for blood glucose concentrations during the first 24 h after PICU admission, both the initial admission glucose value and the mean glucose value over the first 24 h after PICU admission were analyzed. The initial admission glucose values and the mean glucose values over the first 24 h of admission were divided into 6 strata based on cutoff values of 65, 90, 110, 140, and 200 mg/dL (3.6, 5.0, 6.1, 7.8, and 11.1 mmol/L), which were established according to clinical observational and interventional pediatric studies [ 16 , 19 , 22 ]. PICU mortality was calculated for each stratum, and the stratum with the lowest mortality incidence was used as a reference.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the relationship between early blood glucose concentrations and PICU mortality and to define a ‘safe range’ for blood glucose concentrations during the first 24 h after PICU admission, both the initial admission glucose value and the mean glucose value over the first 24 h after PICU admission were analyzed. The initial admission glucose values and the mean glucose values over the first 24 h of admission were divided into 6 strata based on cutoff values of 65, 90, 110, 140, and 200 mg/dL (3.6, 5.0, 6.1, 7.8, and 11.1 mmol/L), which were established according to clinical observational and interventional pediatric studies [ 16 , 19 , 22 ]. PICU mortality was calculated for each stratum, and the stratum with the lowest mortality incidence was used as a reference.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in blood glucose levels were not significant, but there was one case of hyperglycemia (> 11.1 mmol/L) in the intervention group after the first day of treatment. More significant cases of hyperglycemia were observed in previous studies [20,21]. Systemic GCS administration should be considered as a risk factor for children with diabetes with hyperglycemia, even if prescribed as a short course.…”
Section: Discussionmentioning
confidence: 60%
“…Hyperglycaemia can worsen a hyperosmotic state such as uraemia and may predispose a patient to infection. Several studies in recent years have revealed an association with hyperglycaemia and increased morbidity and mortality in intensive care patients although there is still some disagreement on the degree of significance [67][68][69][70][71]. Hyperglycaemia in sepsis is also a poor predictor in noncritical-care hospitalised patients and there have been recent guidelines suggesting point-of-care glucose in all hyperglycaemic hospitalised patients, whether diabetic or not [70].…”
Section: Glucosementioning
confidence: 99%